A metabolomic study of Asian and American Ginseng based on RRLC-QTOF/MS methods. Issue 13 (27th August 2019) - He, Yang-Fang; Cai, Han-Qing; Zhang, Hong-Mei; Ren, Zhi-Hui; Tang, Huan; Li, Yan; Zhou, Xiao-Wei; Liu, Wen-Long; Pei, Jin; Liu, Shu-Ying
Abstract: In order to understand the significant differences in activities and effects between Asian ginseng (ASG) and American ginseng (AMG), it is important to study the correlation between chemical structures and biological activities in the two types of herbs. However, more attention has been paid to the analysis of ginsenosides in previous reports distinguishing between ASG and AMG. There are some other bioactive compounds besides ginsenosides, however, few studies have focused on a systematic comparison of these types of compounds. Two metabolomic methods were developed in this study by qualitative data acquisition using normal phase liquid chromatography mass spectrometry (NPLC-MS) and reverse phase liquid chromatography mass spectrometry (RPLC-MS) respectively, in combination with principal component analysis (PCA). Results show that both NPLC-MS and RPLC-MS-based metabolomic methods are feasible in composition profiling, biomarker screening as well as in discrimination of ASG and AMG. 17 ginsenosides were identified as analytical markers in RPLC-MS-based metabolomic method. In comparison, using NPLC-MS-based method, 5 ginsonosides, two amino acids as well as 1 oligosaccharide were identified as analytical markers. Therefore, RPLC-MS-based metabolomic method exhibits better profiling in ginsenosides, while NPLC-MS-based metabolomic method offers the advantage that multiple active ingredients can be determined simultaneously. The two methods are both helpful in identification of biomarker as well as in discrimination of American ginsengs from Asian ginsengs. Graphical Abstract: